Teachers Self-Efficacy and Instructional Practices as Predictors of Individual Work Performance of Teachers: A Convergent Design - CASIO, FLORELYN; J. Pidor, Sylvia (The Future of Education Journal, 2025)
This study explored the influence of teacher self-efficacy and instructional practices on individual work performance among public elementary teachers in Region XI. Using a mixed-methods approach with a convergent design, the study collected quantitative data through adapted survey questionnaires and qualitative data through in-depth interviews and focus group discussions. The study involved elementary teachers from public schools in Region XI and used statistical tools like mean, standard deviation, and multiple linear regression for quantitative analysis, while thematic analysis was employed for qualitative data. The results showed that teachers' self-efficacy and instructional practices were very high, and both significantly influenced individual work performance. The qualitative phase of the study revealed three essential themes: manifestation of highly efficient teaching, spirit of positivity, and fostering a supportive environment. Additionally, two themes emerged on the role of experiences in shaping teachers' beliefs and attitudes: teaching is a multifaceted profession and strong support systems promote sympathetic working relationships. The integration of quantitative and qualitative findings confirmed the significant influence of teacher self-efficacy and instructional practices on individual work performance. The study also found that experiences shape teachers' beliefs, attitudes, and commitment towards their work, highlighting the importance of supportive environments and teacher efficacy. The convergent design allowed for a comprehensive understanding of the complex relationships between these variables, providing insights into the ways teachers' experiences shape their beliefs and attitudes towards individual work performance. Overall, the study's findings have implications for teacher professional development and school administration.